Effectiveness of transcutaneous electrical nerve stimulation for postoperative pain control in adult surgical patients: an umbrella review protocol. Issue 8 (August 2020) - Veith, Matthew; Beiswanger, Logan; Orozco, Raymundo; Lehtonen, Robert; Jackson, Sheena; Benham, Brian
ABSTRACT: Objective: The objective of this review is to evaluate the effectiveness of transcutaneous electrical nerve stimulators for postoperative pain in comparison to current opioid-centric standard of care in adult surgical patients. Introduction: In recent years, opioid pain medications have presented two major problems: national shortages triggering a pain management crisis and an increase in opioid related deaths. Opioids also have a variety of untoward side effects, complicating pain management in postoperative individuals. Due to these serious issues, this review will investigate the use of transcutaneous electrical nerve stimulation as a non-pharmacological means to control postoperative pain. Inclusion criteria: The review will consider for inclusion all systematic reviews, meta-analyses and research syntheses utilizing transcutaneous electrical nerve stimulation as a primary means of postoperative pain treatment, or those comparing transcutaneous electrical nerve stimulation and the current opioid-centric standard of pain management in the treatment of postoperative pain in adult surgical patients. Methods: This umbrella review will consider all published and unpublished literature, limited to the English language only. Sources of data will be Cochrane Library, JBI Evidence Synthesis, CINAHL and PubMed. Unpublished meta-analyses and systematic reviews will be obtained through ProQuest Dissertations and Theses, the United States National Library of Medicine, and Open Grey: System for Information on Grey Literature in Europe. JBI methodology for study selection, critical appraisal, data extraction and summarizing the data will be utilized to reduce bias and minimize the risk of error in extracting relevant data in the accepted reviews. Systematic review registration number: Pending.